Nanocellulose as a sustainable material for water purification. (16th November 2020) - Ahankari, Sandeep; George, Thomas; Subhedar, Aditya; Kar, Kamal K.
Abstract: The demand for purified water has been increasing day by day. More feasible technologies, including membrane filtration, adsorbents, and so forth have emerged out to be more efficient and cheaper over conventional industrial methods. Nanocellulose, being biodegradable, nontoxic, and sustainable nanofiller exhibits excellent mechanical properties, high aspect ratio, high surface area, and more importantly tunable surface chemistry; is a potential candidate to be employed for water purification. Composite membranes and films for water filtration, constituting of biopolymers have gathered immense interest lately. Compared with its unmodified form, the functionalized NC enhances the compatibility with the matrix and readily forming strong network structures; essential for the formation of channels for better adsorption of impurities and higher water flux. This review highlights some of the recent studies dedicated to making and testing of nanofiltration membranes prepared using nanocellulose and its different functionalized derivatives. Abstract :